Efektifitas Ekstrak Daun Sirsak (Annona muricata L) Dalam Terapi Kanker Payudara Pada Jalur Apoptosis - Ramadhani, Nadhira Tsurayya; Maharani, Putri; Wahono, Shafira; Maharani, Tasya Aulia; Adenina, Masayu Syarinta (Fakultas Kedokteran Universitas Trisakti, 2025)
Breast cancer is one of the leading causes of cancer-related mortality in Indonesia. The number of new breast cancer cases has reached 68,858 cases (16.6%) out of a total of 396,914 new cancer cases. Conventional approaches to cancer therapy include surgery, radiation, and chemotherapy. However, these treatments are often expensive and associated with significant side effects. As a result, various preventive and therapeutic efforts have been developed, including the use of herbal plants with potential anticancer properties such as Annona muricata L. Therefore, a more in-depth review of this compound is needed. This article is based on data retrieved from databases such as PubMed, ScienceDirect, ClinicalKey, and Google Scholar using the keywords: “Annona muricata L.”, “breast cancer”, “acetogenin”, “apoptosis”, and “oxidative stress”. Articles in English or Indonesian within the last 10 years were included. The literature review revealed that Annona muricata L. contains active compounds, primarily acetogenins, which exhibit cytotoxic activity through the induction of apoptosis. Acetogenins act by inhibiting mitochondrial complex I (NADH dehydrogenase), resulting in decreased adenosine triphosphate (ATP) production, energy stress, and subsequently, apoptosis induction. In addition, acetogenins affect the intrinsic apoptotic pathway by downregulating anti-apoptotic proteins such as Bcl-2 and Bcl-xL, while upregulating p53 gene expression, which plays a key role in activating the extrinsic apoptosis pathway. Another mechanism is its ability to reduce oxidative stress by enhancing the activity of antioxidant enzymes, thereby protecting normal cells from free radical-induced damage. However, to date, studies of Annona muricata L. as an adjuvant therapy for breast cancer remain limited—especially regarding its long-term use and effects on normal cells. Therefore, Annona muricata L. holds potential as an adjunct therapy in the treatment of breast cancer. Further research is needed to determine the appropriate dosage, long-term effectiveness, and potential side effects, particularly in breast cancer patients.